Temperature and salinity variability in the Greek Seas based on POSEIDON stations time series: preliminary results - VELAORAS, D.; KASSIS, D.; PERIVOLIOTIS, L.; PAGONIS, P.; HONDRONASIOS, A.; NITTIS, K. (Mediterranean Marine Science, 2013)
Temperature and salinity time series provided by three POSEIDON monitoring stations (buoys) are examined in order to study the seasonal and interannual variability of the water mass characteristics. The sites at Athos (North Aegean Sea), E1M3A (Central Cretan Sea) and Pylos (Eastern Ionian Sea) were chosen, as these buoys provide measurements at various depths, while they represent 3 major basins respectively. The study of the T and S characteristics reveals important seasonal changes and highlights the particular characteristics of each basin. Dense water production in the Northern Aegean is found to be hindered by the presence of the surface Black Sea Water (BSW) mass. On the other hand, the intermediate water mass in the Cretan Sea is shown to be ventilated during the winter season. A significant temperature and salinity increase has been monitored over both the Central Cretan and Eastern Ionian Seas starting from the middle of 2008 and 2009 respectively. This could possibly be attributed to changes in the intermediate water masses of the Eastern Mediterranean, without ruling out the possibility of water mass exchanges between the two basins.